2011
DOI: 10.4141/cjps10073
|View full text |Cite
|
Sign up to set email alerts
|

Breeding for clubroot resistant spring canola (Brassica napusL.) for the Canadian prairies: Can the European winter canola cv. Mendel be used as a source of resistance?

Abstract: 2011. Breeding for clubroot resistant spring canola (Brassica napus L.) for the Canadian prairies: Can the European winter canola cv. Mendel be used as a source of resistance? Can. J. Plant Sci. 91: 447Á458. Canola (Brassica napus L.) cultivars resistant to clubroot disease, caused by Plasmodiophora brassicae, are desired by the Canadian canola growers. Different genotypes of its two parental species B. rapa and B. olaeacea carry resistance to this disease. Furthermore, the European winter canola cultivar Mend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…'Mendel' cross (Rahman et al 2011), were crossed to a clubroot susceptible spring canola line A07-26NR. The microspore culture technique, as described by Kebede et al (2010), was applied on a single plant basis to the F 1 's of A07-26NR 9 1CA0591.323 and A07-26NR 9 1CA0591.263 crosses for the development of 200 DH lines.…”
Section: Doubled Haploid (Dh) Population Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…'Mendel' cross (Rahman et al 2011), were crossed to a clubroot susceptible spring canola line A07-26NR. The microspore culture technique, as described by Kebede et al (2010), was applied on a single plant basis to the F 1 's of A07-26NR 9 1CA0591.323 and A07-26NR 9 1CA0591.263 crosses for the development of 200 DH lines.…”
Section: Doubled Haploid (Dh) Population Developmentmentioning
confidence: 99%
“…Hi-Q were included in the experiments as controls. The inoculated seedlings were kept in a greenhouse at 20-22/15°C day/ night and 16-h photoperiod as described by Rahman et al (2011). The plants, at the age of 6 weeks after inoculation, were scored for the disease symptom using the scale of 0-3 devised by Kuginuki et al (1999), where 0 = no galls, 1 = a few small galls, 2 = moderate galling, and 3 = severe galling.…”
Section: Tests For Clubroot Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Previous work by Rahman et al . () reported statistically significant distorted segregation ratios for resistance to susceptiblility in F 2 and F 3 families. This suggested that clubroot resistance derived from Mendel followed a complex mode of inheritance.…”
Section: Introductionmentioning
confidence: 97%
“…Although there are some commercial clubroot-resistant (CR) canola and cabbage cultivars available, this resistance is associated with single dominant CR genes [11], as reported in Chinese cabbage [12] and oilseed rape [13], and leads to rapid breakdown. Two resistance genes have been isolated from Chinese cabbage ( Brassica rapa), CRa and Crr1 [14,15], while genetic mapping and identification of clubroot resistance has been also achieved in Brassica oleracea [1619].…”
Section: Introductionmentioning
confidence: 99%